Endovascular and open repair of abdominal aortic aneurysm - Schmitz-Rixen, Thomas; Böckler, Dittmar (Deutsches Ärzteblatt, 2020)
An abdominal aortic aneurysm (AAA) is an arterial wall weakness in the abdominal section of the aorta, resulting in changes in flow and pressure conditions in this area which ultimately lead to expansion and bulging of the weakened vessel wall. The...